Ethylene Glycol Toxicity and Its Therapy Management: A Literature Review - Kurniawan, Robi; Hanifah, Suci (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Ethylene glycol (EG) is an antifreeze substance commonly used as an additive for syrup preparations. One of the detrimental effects caused by EG toxicity is acute renal failure (ARF) and death, assuming therapy and management are delayed. Presently, there are limited studies on toxicity of EG and therapy. Therefore, this study aimed to provide an overview of EG toxicity levels, clinical manifestations, arising reactions, and therapy management methods.Objectives: A narrative review design was employed with data collected from PubMed and Google Scholar. The strategy used keywords such as “ethylene glycol toxicity” and "acute renal" with the assistance of Boolean operators including AND and OR.Methods: The result showed that the minimum EG level for toxicity was at 22 mg/dL, followed by metabolic acidosis with an increased anion gap (>10mmol/L). Based on case reports from one experimental study, the clinical manifestations of patients experiencing EG poisoning included decreased consciousness, tachycardia, and coma, with ARF occurring after 24-72 hours.Results: Write study findings in this section.Conclusion: EG poisoning could cause kidney damage in the form of ARF and lead to death, assuming therapy was delayed. Presently, the most effective therapy for EG poisoning was fomepizole.